Interactive effects of situational and enduring involvement with perceived crowding and time pressure in pay-what-you-want (PWYW) pricing - Sharma, Piyush; Roy, Rajat; Rabbanee, Fazlul (Elsevier, 2019)
This paper explores the differences in the interactive effects of situational and enduring involvement with perceived crowding and time pressure on customers' PWYW pricing decisions. Two empirical studies, an online experiment about a hair salon using PWYW pricing and a field survey with customers of a real-life PWYW restaurant, are used to test all the hypotheses. In study one, situational involvement has significant direct and indirect effects on the customers' allocation of internal reference prices to their PWYW prices (RATIO), whereas enduring involvement has a positive (negative) effect under low (high) situational involvement. In study two, both enduring and situational involvement have no significant direct effects on RATIO but situational involvement has a significant negative (positive) effect for participants with low (high) enduring involvement. Besides extending both PWYW and involvement literature, these findings would help managers understand the direct and indirect effects of situational variables on customers' PWYW pricing decisions.